2016
DOI: 10.1007/s40615-016-0325-x
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and Racial Disparities: a Case-Control Study of Patients Receiving Transcatheter Aortic Valve Replacement for Severe Aortic Stenosis

Abstract: Socioeconomic and racial disparities were associated with patients with severe AS receiving TAVR at a major referral center. This study emphasizes the importance of improving access to standard of care for these subgroups of cardiac patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 19 publications
1
53
0
Order By: Relevance
“…Despite lower incidence of severe AS in Black patients [15], they have been shown to have lower chance of being referred for SAVR despite similar severity of aortic disease and comorbidity profile. Reasons for discrepancy in the referral was either due to patient declining the procedure [23] or being lost to follow up [24]. Our study confirms the similar inter-racial periprocedural outcomes, and thus patients should be referred earlier with proper education to help improve cardiovascular care for minorities.…”
Section: Discussionsupporting
confidence: 71%
“…Despite lower incidence of severe AS in Black patients [15], they have been shown to have lower chance of being referred for SAVR despite similar severity of aortic disease and comorbidity profile. Reasons for discrepancy in the referral was either due to patient declining the procedure [23] or being lost to follow up [24]. Our study confirms the similar inter-racial periprocedural outcomes, and thus patients should be referred earlier with proper education to help improve cardiovascular care for minorities.…”
Section: Discussionsupporting
confidence: 71%
“…The transcatheter valve therapy (TVT) registry showed that in 70,221 patients undergoing TAVR, the majority (91%) were Caucasians, whereas African Americans, and Hispanics were 3.8 and 3.4%, respectively 28 . The most likely reasons for this disparity are the relatively lower prevalence of AS in racial minorities, 29 referral and detection bias for AVR favoring Whites over other racial groups, 30,31 and limited access to care due to cultural beliefs, or socioeconomic limitations among minorities 31 . Regardless, in the TVT registry, the adjusted 30‐day and 1‐year outcomes in non‐Whites were comparable with those of Whites, 28 suggesting the benefits of TAVR over SAVR are unlikely to be influenced by racial differences.…”
Section: Discussionmentioning
confidence: 99%
“…A post hoc analysis in a study by Sleder et al (2) revealed that AA patients with severe AS were less likely to be referred to cardiology, more likely to decline an intervention, or be lost to follow-up. Another study showed that fewer cardiac referrals and follow-up appointments were made to Hispanic and AA patients and patients with lower socioeconomic status (34).…”
Section: Disparities In Specialist Referralsmentioning
confidence: 99%
“…Although there have been a few studies (1)(2)(3) examining the influence of race on transcatheter aortic valve replacement (TAVR) procedure rates, this is the first review article to comprehensively summarize this topic whilst proffering solutions on how to reduce such disparities in TAVR implantation.…”
Section: Introductionmentioning
confidence: 99%